Seleksi, Karakterisasi dan Identifikasi Bakteri Pendegradasi 2-(thiocyanomethylthio) benzothiazole (TCMTB) - Sembiring, Langkah; Susilawati, Lela; Suhartanti, Dwi (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
The objective of this research was to investigate the capabilities of bacteria isolated from industrial tanning waste to degrade TCMTB. The bacteria was initialy screened, based on their tolerance to various concentration of TCMTB using paper disk method. Then, those strains were further analyzed in terms of their ability to produce ammonia (NH4+) and sulphate (SO42-). Degradation activity was measured based on remaining residue of TCMTB analyzed using HPLC. The superior strain that showed the highest activity in degradation of TCMTB then were characterized and identified based on phenotypic and 16S rDNA sequence analysis. The result of the experiments showed that four selected strains among seven were choosen based on their high tolerance to various concentration of TCMTB, namely PK1, PK2, PK4 and PK6. All four strains showed the ability to produce ammonia and sulphate but three of which, namely PK2, PK4 and PK6 showed the high capability to degrade TCMTB. One particular strain (PK2) was observed to degrade TCMTB 40.8% within 7 days, but the others were less than 30%. Based on the phenotypic characteristics and 16S rDNA sequence analysis, the best strains (PK2) was identified to be member of genus Pseudomonas.